2012
DOI: 10.1007/s11207-012-0118-2
|View full text |Cite
|
Sign up to set email alerts
|

Helium Emissions Observed in Ground-Based Spectra of Solar Prominences

Abstract: The only prominent line of singly ionized helium in the visible spectral range, He II 4686 Å, is observed together with the He I 5015 Å singlet and the He I 4471 Å triplet line in solar prominences. The Na D 2 emission is used as a tracer for He II emissions which are sufficiently bright to exceed the noise level near 10 −6 of the disk-center intensity. The prominences thus selected are characterized by small non-thermal line broadening and almost absent velocity shifts, yielding narrow line profiles without w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Ramelli et al (2012) find a small reduced width of Δλ D /λ 0 (4571) = 0.9 × 10 −5 . We verified this at Locarno in Oct. 2013 and again find Δλ D /λ 0 = 1.0 × 10 −5 .…”
Section: Magnesium Linesmentioning
confidence: 81%
See 3 more Smart Citations
“…Ramelli et al (2012) find a small reduced width of Δλ D /λ 0 (4571) = 0.9 × 10 −5 . We verified this at Locarno in Oct. 2013 and again find Δλ D /λ 0 = 1.0 × 10 −5 .…”
Section: Magnesium Linesmentioning
confidence: 81%
“…Recently, Ramelli et al (2012) and Wiehr et al (2013) resumed such observations and found that "cool" emissions (e.g. of Na D or Mg b) are accompanied by rather broad Table 3, here with error bars).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Prominence emission lines are superposed by parasitic light originating from imperfect telescope optics (rather than from Earth's atmosphere; see Stellmacher & Wiehr, 1970). We take spectra of the "aureola" in the immediate (emission-free) prominence neighborhood with almost the same slit inclination to the solar limb.…”
Section: Data Reductionmentioning
confidence: 99%